Epidemiology of intracerebral hemorrhage: A systematic review and meta-analysis - Wang, Sai; Zou, Xue-Lun; Wu, Lian-Xu; Zhou, Hui-Fang; Xiao, Linxiao; Yao, Tianxing; Zhang, Yupeng; Ma, Junyi; Zeng, Yi; Zhang, Le (Frontiers in Neurology, 2022)
Background: Intracerebral hemorrhage (ICH) is associated with high mortality and disability rates. This study aimed to investigate the relationship between sex, age, study year, risk factors, bleeding site, median year of study, and the incidence of ICH. Method: Literature on the incidence of ICH published on January 1, 1980, and January 1, 2020, was systematically retrieved from PubMed and Embase databases. The random-effects model and subgroup analysis were used to explore the relationship between the incidence of ICH and different ages, sex, bleeding sites, and risk factors. Results: We summarized the epidemiological changes in ICH in the past 40 years according to 52 studies and found that the total incidence of ICH is 29.9 per 100,000 person-years (95% confidence interval [CI]:26.5-33.3) people, which has not decreased worldwide. The incidence of ICH in the Asian population is much higher than in other continents. In addition, the incidence of ICH increases with age and differs at the 85-year-old boundary. Males are more likely to develop ICH than females, and the basal ganglia region is the most common area for ICH. Of the 10 risk factors examined in this study, those with hypertension had the highest incidence of ICH, followed by those with excessive alcohol consumption and heart disease. Conclusion: The prevention and treatment of ICH still need to be improved continuously according to age, sex, risk factors, and other factors, and targeted and normative strategies should be gradually developed in the future.